Ciclones extratropicais e precipitação associada no hemisfério sul: clima presente e futuro - Souza, Marcelo Rodrigues de (2023)
Extratropical cyclones are one of the main mechanisms for transporting heat and moisture at mid and high latitudes in the Southern Hemisphere (SH), playing a crucial role in defining weather and climate in these regions. Given their relevance, it is important to understand how cyclones and associated precipitation will respond to climate change in the future. Thus, the main objective of this study is to evaluate the climatology of extratropical cyclones and associated precipitation in the present (1979-2014) and future climate (2070-2099), considering the SSP5-8.5 climate scenario. Data from an ensemble of five CMIP6 (Coupled Model Intercomparison Project Phase 6) models, the ERA5 reanalysis, and GPCP (Global Precipitation Climatology Project) observational data were used. To identify cyclones and fronts, two automated algorithms based on the relative vorticity field and equivalent potential temperature at 850 hPa were used, respectively. Although underestimating the total cyclone frequency in the SH compared to ERA5 both in winter and summer, CMIP6 adequately represented the main patterns of cyclone track density distribution in the present climate. Maximum densities in winter were found between the South Atlantic and Indian Ocean and near the Antarctic coast, south of Australia and New Zealand. In summer, the track density acquires a more zonal pattern, concentrated between 40°S and 65°S. CMIP6 models performed well in estimating the average lifetime of cyclones but presented less intense and slower systems compared to ERA5. Regarding precipitation associated with cyclones, composite analyses showed that the highest precipitation rates occur near fronts and cyclone centers. Overall, CMIP6 showed good performance in representing the spatial and temporal patterns of precipitation associated with cyclones, especially in winter. For the future climate, decreases of about 4% in the seasonal average cyclone frequency are projected for all ocean basins in the SH, except for the Antarctic Ocean. Projections indicate an increase in the average speed and total displacement of cyclones in the SH in both seasons. Composite analyses show that CMIP6 projects an increase in associated precipitation at all stages of the cyclone lifecycle in the future for both extreme and moderate cyclones, especially in frontal regions. Regarding future changes in distribution and magnitude of precipitation associated with the main system categories assessed in this study, CMIP6 projects: (i) CExt (center of extratropical cyclones): reduction of associated precipitation from 45°S (60°S) equatorward in winter (summer) and an increase poleward; (ii) Cold fronts: increase between 40°S and 55 (45°S and 60°S) in winter (summer), approximately, and reduction equatorward in both seasons; (iii) Warm fronts: similar changes to CExt, but of lower magnitude; and (iv) CExt + fronts: robust increases in precipitation associated with the combination of CExt and fronts at mid and high latitudes and maximum reduction in regions characterized by semi-permanent subtropical anticyclones.